Da‘wah Communication in the Concept of Amr Ma‘ruf Nahi Munkar: A Thematic (Maudhu‘i) Qur’anic Exegesis on Social Transformation - Br. Barus, Liza Nuarida Ulfah; Abdullah (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article examines the Qur’anic concept of amar ma‘ruf nahi munkar using a thematic exegesis (tafsīr mawḍū‘ī) approach to explore its relationship with social transformation. This study is a library-based research project, using the Qur’an as the primary source and classical/modern tafsīr works as well as supporting scholarly literature as secondary sources. The analysis was conducted by collecting relevant verses, organizing them into themes, and then synthesizing exegetical perspectives thematically. The findings show that amar ma‘ruf nahi munkar functions as a framework of social ethics that encourages personal moral improvement, strengthens a communal culture of virtue, and contributes to a more just and public-welfare-oriented social order